Arab Republic of Egypt : Client Perspectives on Elements of World Bank Support - Sakr, Sakr Ahmed (World Bank, Washington, DC, 2021)
The present study summarizes the findings of a study on the World Bank (Bank) operations in Egypt. It aims at gathering knowledge and information from Egypt and the clients in Egypt on the relevance and effectiveness of the Bank operations in meeting Egypt's development objectives and reducing poverty, how effective does the Bank use knowledge sharing in its engagement with the country, and to what extent has the Bank support helped Egypt to contribute to identified global priorities and initiatives. The study is based on interviews, the key Bank reports, plus some additional sources from The International Monetary Fund (IMF), United Nations Development Program (UNDP), Egypt Human Development Report (EHDR) 2005, the Ministry of Planning and the Kuwait Fund for Arab Economic Development (KFAED) appraisal reports.